SERTAD3 induces proteasomal degradation of ZIKV capsid protein and represents a therapeutic target. Issue 2 (13th January 2023) - Sun, Nina; Zhang, Rong‐Rong; Song, Guang‐Yuan; Cai, Qiaomei; Aliyari, Saba R.; Nielsen‐Saines, Karin; Jung, Jae U.; Yang, Heng; Cheng, Genhong; Qin, Cheng‐Feng
Abstract: Zika virus (ZIKV) is a mosquito‐borne RNA virus that belongs to the Flaviviridae family. While flavivirus replication is known to occur in the cytoplasm, a significant portion of the viral capsid protein localizes to the nucleus during infection. However, the role of the nuclear capsid is less clear. Herein, we demonstrated SERTA domain containing 3 (SERTAD3) as an antiviral interferon stimulatory gene product had an antiviral ability to ZIKV but not JEV. Mechanistically, we found that SERTAD3 interacted with the capsid protein of ZIKV in the nucleolus and reduced capsid protein abundance through proteasomal degradation. Furthermore, an eight amino acid peptide of SERTAD3 was identified as the minimum motif that binds with ZIKV capsid protein. Remarkably, the eight amino acids synthetic peptide from SERTAD3 significantly prevented ZIKV infection in culture and pregnant mouse models. Taken together, these findings not only reveal the function of SERTAD3 in promoting proteasomal degradation of a specific viral protein but also provide a promising host‐targeted therapeutic strategy against ZIKV infection.